Urban Communities, Housing Commons, and Real Estate Investment: Revisiting Housing Cooperative Development in Senegal Since the Beavers Experiment - Claire Simonneau; Serigne Mansour Tall; Momar Diongue (International Journal of the Commons)
Since the 2000s, the renewed interest in housing cooperatives in the Global South has ascribed to them a number of virtues: a successful mechanism for mutual aid and escape from poverty, a “third way” in the face of the failures of public production and the speculative excesses of private production. However, there is a lack of empirical studies documenting the concrete development and operations of housing cooperatives. This article aims to contribute to studies on housing cooperatives by examining their history and implementation in Senegal, drawing on the literature and first-hand data from interviews and case studies in the Dakar region. Senegalese housing cooperatives occupy a unique place in the West African cooperative landscape given their longevity since the late 1950s and the political and militant support they periodically receive. More specifically, we examine both shifts in the institutional support to cooperatives in Senegal, and shifts in understandings and practices of solidarity along Senegal’s socio-political transformations. This provides a nuanced picture of Senegalese cooperative. They have been the leading producer of formal housing in Senegal over the past decades. Nevertheless, the cooperative movement is weaker today, despite a public support in political discourse. Finally, current cooperative production leaves little room for the principles of sustainable communities beyond the step of land acquisition, for collective commitment to long-term maintenance, and for intergenerational affordability of land and housing.